STRATEGY TO RAISE BRAND AWARENESS USING SOSIAL MEDIA TO THE MILENIALS - Putu Sukma Wardani; I Gede Sanica (Jurnal Bisnis Terapan, 2020)
Social media as a digital marketing channel is currently utilized as a promotional media for business people especially those who choose the millennial generation segment as their main target market. The growth in the number of social media users today is also seen as an opportunity to build brand awareness through social media. This research sets its objective to determine strategies in raising brand awareness with social media marketing on Instagram for the millennial generation. This research focuses on social media marketing that has been applied to the Il's Project brand which is one of the local footwear brands in the city of Denpasar. Using a qualitative approach, with a descriptive analysis of this study collecting data through interviews, observations and documentation which is further analyzed by SWOT analysis techniques comparing internal and external factors to determine the SWOT Matrix and IE Matrix for strategy determination. The results showed, Il's Project social media marketing was in quadrant 1 in the SWOT Matrix, and cell 5 in the IE Matrix. The right strategy is to support an aggressive strategy and growth strategy, namely, market penetration, increased sales and profits and increased marketing effectiveness on social media.